2001
DOI: 10.1542/peds.108.5.e93
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil-Associated Inflammation and Elaboration of Eosinophil-Derived Proteins in 2 Children With Raccoon Roundworm (Baylisascaris procyonis)Encephalitis

Abstract: ABSTRACT. Objective. Eosinophil-associated proteins, especially eosinophil-derived neurotoxin, may be important contributors to the neurologic pathology and symptoms caused by Baylisascaris procyonis infection.Methods. Two cases of severe B procyonis encephalitis with evidence of marked eosinophil degranulation in the central nervous system are presented. Serial cerebrospinal fluid (CSF) specimens were collected from each patient during the course of their illness. Antibodies against B procyonis were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 20 publications
0
44
0
Order By: Relevance
“…Immunofluorescence studies suggest that eosinophilic material surrounding migration tracks, larvae, and perivascular areas consists of eosinophil major basic protein arising from eosinophil degranulation (23). Moertel et al and others demonstrated markedly increased CSF levels of eosinophil major basic protein, eosinophil-derived neurotoxin, and interleukin 5, a critical cytokine involved in eosinophilia and the eosinophilic response to helminth parasites, in two fatal cases of B. procyonis NLM (35,41,49). At autopsy, larvae have been identified in cerebrum, cerebellum, and spinal cord, with and without surrounding inflammatory reaction.…”
Section: Pathologymentioning
confidence: 95%
See 2 more Smart Citations
“…Immunofluorescence studies suggest that eosinophilic material surrounding migration tracks, larvae, and perivascular areas consists of eosinophil major basic protein arising from eosinophil degranulation (23). Moertel et al and others demonstrated markedly increased CSF levels of eosinophil major basic protein, eosinophil-derived neurotoxin, and interleukin 5, a critical cytokine involved in eosinophilia and the eosinophilic response to helminth parasites, in two fatal cases of B. procyonis NLM (35,41,49). At autopsy, larvae have been identified in cerebrum, cerebellum, and spinal cord, with and without surrounding inflammatory reaction.…”
Section: Pathologymentioning
confidence: 95%
“…The first confirmed cases of NLM in humans were described to have occurred in two young boys, in 1984 and 1985 (16,25). Since that time, another 11 confirmed human cases have been documented (Table 1) (8,10,18,41,44,47,51). An earlier (1975) unconfirmed case of NLM involved an 18-month-old girl with geophagia from Missouri, who presented with acute hemiplegia, cerebrospinal fluid (CSF) and peripheral eosinophilia, and elevated isohemagglutinins (1).…”
Section: Historical Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein epitopes of 33-kDa to 45-kDa antigens appear to be recognized selectively by antibodies from B. procyonis-infected humans and animals but not by normal human or T. canis antibody-positive sera . In addition, children with clinical B. procyonis NLM are strongly positive for anti-Baylisascaris antibodies in CSF and serum and have consistently been negative for anti-Toxocara antibodies (Cunningham et al, 1994;Fox et al, 1985;Gavin et al, 2002;Kazacos, 2001;Moertel et al, 2001;Murray, 2002;Park et al, 2000;Rowley et al, 2000). In several of these cases, positive B. procyonis serology was confirmed by brain biopsy or at autopsy (CDC, 2002;Fox et al, 1985;Huff et al, 1984;Rowley et al, 2000).…”
Section: Serologymentioning
confidence: 99%
“…In several of these cases, positive B. procyonis serology was confirmed by brain biopsy or at autopsy (CDC, 2002;Fox et al, 1985;Huff et al, 1984;Rowley et al, 2000). Acute and convalescent-phase titers characteristically demonstrate several fold increases in both serum and CSF anti-Baylisascaris antibody levels (Gavin et al, 2002;Moertel et al, 2001). …”
Section: Serologymentioning
confidence: 99%